Proposal of a solar photovoltaic system for the reduction of energy consumption in a hatchery - Castillo Álvarez, Yoisdel (2023)
The following study aims to evaluate the proposal of a solar photovoltaic system with a view to reducing energy consumption in a hatchery. The proposed system is composed of 3 strings of 18 modules connected in series of the DSM-380MP type occupying a useful area of 105 m2. The photovoltaic solar system is accompanied by an inverter model TRIO-20_0-TL-OUTD-S1-US from ABB with an output of 22 kWac. The solar photovoltaic system has an annual generation capacity of 29,068 MWh/year. Since the plant has an annual generation capacity of 29,068 MWh/year average annual consumption for the case study is about 100 MWh/year, it is possible to substitute approximately 30% of this consumption by using the FVSS. Considering one of the minimum costs of the international market for the FVSS of 32 060,45 $CUP, the investment presents a NPV of $ 741 728,91, after 25 years, an Investment Recovery Period (IRP) of 1 year and an Internal Rate of Return (IRR) of 172%.